Legal Reconstruction of the Cancellation of Unused Trademarks: A Study of Commercial Court Judgments and Supreme Court Decisions - Sofyan Sauri; Suherman Suherman; Iwan Erar Joesoef (International Publisher, 2026)
The cancellation of unused trade marks is a key instrument within the trade mark legal system for preventing the hoarding of trade marks and safeguarding the function of trade marks as active commercial identities in trade. Although Pasal 74 UU No. 20 Tahun 2016 on Trade Marks and Geographical Indications sets out the mechanism for cancelling trade marks on the grounds of non-use, this provision does not provide clear parameters regarding the standard of use required for a trade mark to be legally maintained. Consequently, there is inconsistency in interpretation within judicial practice, as reflected in the differing legal reasoning between the Decision of the Central Jakarta Commercial Court No. 45/Pdt.Sus-HKI/Merek/2023/PN.Niaga.Jkt.Pst and the Decision of the Supreme Court No. 76 K/Pdt.Sus-HKI/2024. This study analyses the mechanisms for the cancellation of unused trade marks in Indonesia in comparison with those in the United States and China, and formulates a legal reconstruction to achieve legal certainty using normative legal methods and legislative, case-law, conceptual and comparative legal approaches. The research findings indicate that the lack of clarity regarding the concept of ‘genuine use’ in Indonesian trade mark law leads to legal uncertainty in the assessment of trade mark use. The United States has developed a more measurable standard of ‘use in commerce’ through the ‘Affidavit of Use’ mechanism, whilst China has implemented an efficient administrative cancellation system through the China National Intellectual Property Administration (CNIPA). Based on Gustav Radbruch’s theory of legal certainty, this study recommends the revision of Pasal 74 UU No. 20 Tahun 2016 Trade Marks and Geographical Indications Act by regulating the parameters of ‘genuine use’ and implementing a mechanism for the periodic reporting of trade mark use, with a view to enhancing legal certainty, procedural efficiency and the effectiveness of trade mark protection in Indonesia.